Tuberculosis - Ntumba Kayembe, Jean-Marie (IntechOpen, 2018)
Tuberculosis is an ancient disease with a high incidence and mortality rate, unequally distributed worldwide. Epidemiological indicators, but also risk factors, play a key role in the natural history of the disease and need to be regulary addressed. Low and middle income countries are not prepared for appropriate response and are also the most affected. The incidence of this extrapulmonary disease is far from being clearly established. Epidemiological studies in different geographical areas will help in this field.